Election worry, political identity, and subsequent physical health in the United States - Daniel P. Relihan; Kayley D. Estes; Branislav Jovanovic; Dana Rose Garfin; Roxane Cohen Silver; E. Alison Holman (SSM - Mental Health, 2025)
Political polarization surrounding elections may have population-level physical health consequences over time. Given that psychological distress is associated with worse physical health, heightened election-related worry (a.k.a. election worry) may have negative physical health implications for the U.S. population. We assessed the prospective association between worry about the 2020 presidential election and new onset physical health ailments over the subsequent 3 years in a nationally representative U.S. sample (N = 4,311) and examined differences by political identity. Our longitudinal cohort study used the probability-based NORC AmeriSpeak Panel. Baseline physician-diagnosed mental and physical health conditions, smoking, political identity, and demographics were assessed pre-2020, with new-onset physical health ailments (e.g., heart problems, cancer, stroke) reassessed in Spring 2022 and Summer 2023. Election worry was measured in September–October 2020; political identity and demographics were updated Fall 2021. Adjusting for demographics, baseline health conditions, smoking, health insurance coverage, and prior mental health diagnosis, each one-unit increase in 2020 election worry was associated with 12% higher odds of developing any new-onset physical health ailments (OR = 1.12, 95% CI[1.01, 1.24], p = .026) over the subsequent 3 years. This association was significantly stronger for Republicans compared to Democrats (OR = 1.28, 95% CI[1.01, 1.62], p = .038). These findings suggest that election worry may be a social determinant of health with measurable physical health consequences, particularly among those whose political party loses the election. Understanding these dynamics is crucial for developing interventions to mitigate the health impacts of political stress in an increasingly polarized society.